2022
DOI: 10.1111/1346-8138.16687
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 vaccine‐triggered conversion from systemic lupus erythematosus (SLE) to bullous SLE and dipeptidyl peptidase 4 inhibitors‐associated bullous pemphigoid

Abstract: Systemic lupus erythematosus (SLE) and bullous pemphigoid (BP) are chronic autoimmune diseases in which autoantibodies (auto-Abs) with different specificities are implicated in the induction and progression of these diseases. A few cases of coexistent SLE and BP or conversion from SLE to BP have been reported in the literature. 1,2 It has recently been reported that SARS-CoV-2 mRNA vaccines could trigger the development of new-onset BP or BP flares in a patient with bullous LE 3,4 while both new-onset and flar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Previous case reports and case series have reported 164 cutaneous AEs in 161 patients. Two cases with multiple cutaneous AEs were of patients with lupus (SLE and LEP), and, interestingly, both cases showed worsening of the lupus symptoms 2 weeks after vaccination, and another cutaneous AE developed several months later 53,56 . Among the 142 vaccinated cases with age data, there was no significant difference in the onset age between men and women.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous case reports and case series have reported 164 cutaneous AEs in 161 patients. Two cases with multiple cutaneous AEs were of patients with lupus (SLE and LEP), and, interestingly, both cases showed worsening of the lupus symptoms 2 weeks after vaccination, and another cutaneous AE developed several months later 53,56 . Among the 142 vaccinated cases with age data, there was no significant difference in the onset age between men and women.…”
Section: Discussionmentioning
confidence: 88%
“…A total of 164 non‐injection‐site reactions in 161 patients have been reported in previous case reports and series 7–88 . Patients with systemic lupus erythematosus (SLE) and lupus erythematosus profundus (LEP) showed exacerbation of lupus eruptions after 2 weeks, and other AEs developed several months later.…”
Section: Resultsmentioning
confidence: 99%
“…62 Moreover, a diabetic 71-year-old male with a history of hemophagocytic lympho-histiocytosis with no known trigger that occurred 1 year earlier presented with blistering lesions on the neck and wrist along erythematous plaques over the face. 63 Besides, serological tests were positive for ANA, anti-Smith antibodies, and anti-dsDNA antibodies, together with low complement levels supporting the diagnosis of SLE. At the time, studies have shown concerns about COVID vaccines exacerbating SLE flares.…”
Section: Covid-19 Vaccines and Slementioning
confidence: 95%
“…However, some BP patients had pre-existing neurological or psychiatric disorders, such as dementia, depression, or Alzheimer's disease, which are known to be associated with the development of BP [28,114,115]. Additionally, dipeptidyl peptidase 4 (DPP-4) inhibitors, a well-established risk factor for BP [116], were used by some patients [34,44,45,48]. In the majority of cases, patients denied any new medication use.…”
Section: Other Potential Non-vaccine Triggersmentioning
confidence: 99%
“…In the new onset group, BP patients with limited involvement were treated with topical corticosteroids, while those with more extensive involvements received a variety of systemic immunomodulators, including corticosteroids, doxycycline, nicotinamide, methotrexate, azathioprine, cyclosporine, mycophenolate mofetil, cyclophosphamide, dapsone, colchicine, or hydroxychloroquine [5,6,14,15,28,31,32,35,38,39,[42][43][44][45]49,51,53,56,[70][71][72][73]75,77,82,86,87,92,93]. DPP-4 inhibitors were suspended in patients using these medications [34,44,45,48]. Intravenous immunoglobulin G (IVIG) was administered in selected cases, and biologics, such as dupilumab and omalizumab, were utilized [26,34,49,55,56].…”
Section: Treatment and Outcomes For New-onset Aibd Or Aibd Flaresmentioning
confidence: 99%